KARAKTERISTIK PENGEMBANGAN EKONOMI LOKAL BERBASIS PRODUKTIVITAS KOPI ROBUSTA DI DESA BATU KEBAYAN LAMPUNG BARAT - Aprilia, Annisa; Rahman, Yudha; Aprildahani, Baiq Rindang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2024)
One area that has the potential for local economic development is Batu Kebayan Village, West Lampung Regency. Batu Kebayan Village has various potentials, especially in the field of coffee productivity, but this is still not optimal because it still has various limitations including the need for capital support in processing land and infrastructure; policies that are still inconsistent; and the lack of public interest in buying processed coffee products and lack of promotion. The approach used in this research is a deductive research approach with the analytical technique used in the form of a combination of qualitative descriptive analysis and factor analysis. The data collection method in this study used primary data collection techniques (open interviews and observations). The results obtained from this study are based on the results of the analysis on targets regarding the characteristics of local economic development, found various potentials that support local economic development based on robusta coffee productivity. However, to support this, it is necessary to increase the processing of production products that are not yet optimal, as well as improve road infrastructure to the plantation location.